Review paper Functional studies of genes involved in pathogenesis of aspirin-induced asthma - Kacprzak, Dorota; Pawliczak, Rafał (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
About one fifth of asthmatics have aspirin intolerance. There are several theories explaining pathogenesis of aspirin-induced asthma (AIA). According to the cyclooxygenase theory, aspirin inhibits cyclooxygenase enzymes leading to prostaglandins (PGs) biosynthesis inhibition. In turn, deficiency of PGE 2 has been considered as a triggering factor, resulting in overproduction of proinflammatory leukotrienes and therefore resulting in typical clinical symptoms. Equally important hypothesis seems to be 15-hydroxyeicosatetranoic acid release and diminished production of anti-inflammatory lipoxins after aspirin challenge. In the literature, there is also a lot of data about genetic mechanisms suggesting various gene involvement. This review presents a profile of genes whose involvement in the pathogenesis of bronchial asthma with aspirin hypersensitivity has been verified at the level of RNA and protein expression. Simultaneously, we have discussed several genes whose participation in the AIA is not completely understood due to the lack of functional studies.